PEMANFAATAN DANA CORPORATE SOCIAL RESPONSIBILITY BANK SYARIAH MANDIRI CABANG KENDARI - Muhamad Turmudi (Institut Agama Islam Negeri Kendari, 2018)
This study examines a Corporate Social Responsibility Program of Syariah Banking so as to provide an understanding of the existence, implementation and source of funds of social programs developed through the utilization of corporate social responsibility funds in Islamic banking institutions especially at Bank Syariah Mandiri Branch of Kendari. This study is limited to the management and utilization of corporate social responsibility funds in 2017. The existence of corporate social responsibility program undertaken by Bank Syariah Mandiri Branch of Kendari in 2017 was under the theme of BSM Mengalirkan Berkah. The implementation of this program conducted until October 2017 were (1) mosque development activities with the Rp. 200 million as the funding with such details as 2% for Program Preparation, for direct assistance mosque taking up to 60%, for other assistance up to 30%, for Assistance program as much as 6%, and for monitoring and evaluation up to 2%. (2) Donations for mosques that are used as the place of doing a lot of dawn worship programs (3) Provision of clean water (4) Scholarship program for students. Furtherore, the funding of Corporate social responsibility programs which is channeled to the community comes from zakah funds, corporate profits and the fund of virtue (Qardh al-hasan).